2023
DOI: 10.1186/s13002-023-00578-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in homegardens in relocation villages, a case study in the Baiku Yao area in Southern China

Abstract: Background Baiku Yao is an ancient branch of the Yao people in China who have the custom of maintaining homegardens. The local government has relocated some villagers to improve their livelihood. To study the characteristics of Baiku Yao homegardens and the impact of relocation, we conducted an ethnobotanical study on homegardens in the relocated villages of Huaili and Yaozhai and in the ancient villages of Yaoshan and Duonu from January 2019 to May 2022. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Mandatory relocations accounted for 3% of the migration flows. They could have been supported by long-term governmental policies [36] or occurred in more violent processes [37]. For 13% of the migration flows, we could not identify the main reason for the migration.…”
Section: How Migrations and Food Plants Are Being Studiedmentioning
confidence: 94%
See 2 more Smart Citations
“…Mandatory relocations accounted for 3% of the migration flows. They could have been supported by long-term governmental policies [36] or occurred in more violent processes [37]. For 13% of the migration flows, we could not identify the main reason for the migration.…”
Section: How Migrations and Food Plants Are Being Studiedmentioning
confidence: 94%
“…Lindl. [36]. In arid and semi-arid regions from Benin, people who did internal migrations cultivate vegetables such as Abelmoschus esculentus (L.) Moench., Corchorus olitorius L., S. macrocarpon L., Vernonia amygdalina Delile; fruits (e.g.…”
Section: Migration Effects On Plant Management Knowledge and Usementioning
confidence: 99%
See 1 more Smart Citation
“…However, even if the community has a large home garden land and has a good economic ability to buy home garden land, if the awareness of the importance of green open space around the house is low, their home garden has a narrow size because almost all the land around the house is used. In addition, there is still a lack of understanding about the importance of home gardens or green open spaces, even though home gardens help mitigate environmental change, enable farmers to ensure food availability, protect the origin of species, and improve biogeochemical processes (Hu et al 2023), and improve aesthetics. A recent study reported that home garden owners have significantly higher life satisfaction and mental well-being than non-home garden owners due to intergroup differences in sociodemographic factors (e.g., higher income), time spent outside the home (e.g., longer working hours), and personality traits (e.g., less neuroticism) (Lehberger and Sparke 2023).…”
Section: Description Of the Home Gardenmentioning
confidence: 99%
“…Learning and protecting traditional knowledge related to gardens can promote biodiversity conservation and maintain local livelihoods [ 19 , 21 ]. Additionally, the reasons for potential differences in homegarden plants and traditional knowledge between different communities need to be further elucidated [ 22 ].…”
Section: Introductionmentioning
confidence: 99%